Waqf accounting practices by Malaysian Islamic religious councils / Siti Rokyah Md Zain, Ros Norita Abd Samad and and Nor Ashikin Yusof - Md Zain, Siti Rokyah; Abd Samad, Ros Norita; Yusof, Nor Ashikin (Research Management Institute (RMI), 2012)
Issues related to the administration anddevelopment of waqf properties have been the centre of discussion among Islamic scholars. The objective of this study was to investigate the accounting of waqf assets as practiced by the State Islamic Religious Councils (SIRCs) in Malaysia. The study examined the perception of respondents who were involved directly in managing waqf. Ten self-developed questionnaires were posted to each of the 14 SIRCs in Malaysia. A total of 56 officers responded to the questionnaire. The result indicated that SIRCs did not maintain proper waqfassets accounts, which consequently delayed their financial reports. Generally, there were no allocation of depreciation and 110 evidence of separate accounts for specific waqf and general waqf. The paper contributes towards a deeper understanding of waqf accounting as being practiced by SIRCs, hence, providing a good foundation for ways to improve the reporting and management of waqf assets.